The European Psychiatric Association: Mission, Structure and Perspectives - Gaebel, W.; Falkai, P. (Die Psychiatrie, 2014)
The European Psychiatric Association (EPA) is an association of individual members and national psychiatric societies with the aim to improve mental health care in Europe. In the last years, EPA has developed from an association of individuals into a representative stakeholder for European psychiatry and European psychiatrists. EPA is well connected with other stakeholders in the field of European psychiatry. To make good use of the potential of experts and experiences in the EPA in order to improve mental health care in Europe will be a challenge for the next years.
Keywords: Mental health care; European psychiatry; early career psychiatrists; psychiatric associations; quality indicators; guidance